Measurement Eccentricity the Moon’s Orbit with Image Analysis Technique by Using Tracker Software - Tanzilla, Ricka; Jauhari, Ishafit; Pramudya, Yudhiakto (Universitas Ahmad Dahlan, 2018)
One of the interesting physical phenomenon to be studied is about eccentricity of the Moon's orbit on the movement of the Earth and the Moon as explained in Kepler's Law. In order to explain the phenomenon,several research has been done to determine the measurement accuracy of Moon disk diameter using Trackers and to know the result of the eccentricity value in the application of Kepler's Law. This research can produce eccentricity values accordance with the application of Kepler’sLaw. The research method used is Image Analysis Techniqueassisted with Tracker. The result of this research shows that the eccentricity value obtained is 0.07 ± 0.01. This is in accordance with Kepler's first Law which stated that orbits of each planet and satellite is an ellipse and has an eccentricity value of 0 <e <1. The value of eccentricity obtained has accuracy of 22%,if it compared with the actual value.Whereas, if it compared with the value of ephemeris then the value of accuracy is 8%.